(untitled) (American Journal of Business Management, Economics and Banking, 2023)
Inclusive growth has been a popular concept globally in recent years to address the problems of growing inequality, social disparity and environmental degradation. Raising the standard of living of the population is the primary goal of the state economic policy. The first condition and way to achieve this goal is to ensure economic growth. Economic growth must be inclusive. In recent years, essential reforms aimed at promoting inclusive growth and increasing the welfare of citizens have been implemented in Uzbekistan. This scientific article examines the situation and problems of the Republic of Uzbekistan in achieving inclusive growth, as well as the analysis of the index of inclusive growth.